'Things that you can't really suppress': Adverse childhood experiences in the narratives of people with opioid use disorder - Sydney M. Silverstein; Josef Rivera; Danielle Gainer; Raminta Daniulaityte (Elsevier, 2023)
While numerous studies have established relationships between Adverse Childhood Experiences (ACEs) and adult substance use, few qualitative studies have explored the differing ways in which experiences of childhood adversity are emplotted into narratives of drug use and recovery. This paper analyzes qualitative data collected as part of a mixed-methods longitudinal study of people with opioid use disorder. Narratives of adverse childhood experiences emerged unprompted. After coding qualitative data for mention of ACEs, we thematically analyzed coded data using a framework of critical phenomenology and constructed a four-part typology to differentiate the ways that ACEs were emplotted into narratives. Our four sub-types-which we call 'haunted by trauma', 'seeking redemption', 'casual mentioners', and 'reckoning with inevitability'-did not necessarily cleave along types or number of ACEs, but rather by the manners in which these experiences were conditioned by subsequent life trajectories, and the social, structural, and interpersonal factors that contextualized them. While participants often linked experiences of childhood adversity to adult opioid use, we argue that the differing ways in which individuals understand and process these linkages has implications for both clinical and therapeutic practice. For frameworks like trauma-informed care to be meaningful, we must pay closer attention to these meaningful differences.